Azithromycin-induced QT prolongation in elderly patient - Russo, V.; Puzio, G.; Siniscalchi, N. (Acta Biomedica Atenei Parmensis, 2006)
The authors present a case of an elderly patient with idiopathic dilated cardiomyopathy who developed a significative prolongation of the QT interval after two days of treatment with azithromycin for a community-acquired pneumonia. QT prolongation is associated with a high risk of serious ventricular tachyarrhythmias. Three days after discontinuation of azithromycin, QT interval returned to the normal value.